Kor sukarelawan siswa siswi (SUKSIS) Universiti Malaysia Pahang (UMP) system - Mohd Fadhli, Mat Ideris (2014)
This work introduces the SUKSIS UMP System, to facilitate coach store data of all members, send information SUKSIS activities easily and quickly. Therefore, SUKSIS UMP System will be created as a way to replace the system manually. This system is awaked by commit the PDA use which communicated with the computer. By using the SDLC model (Software Development Life Cycle), SUKSIS UMP System was built through five software development phase. In three first phase, analysis and analysis for the uer requirement will be executed and for two following phase, design and execution will be executed to build SUKSIS UMP System which last.